Analisis Nilai Sun Protection Factor Krim Tabir Surya Ekstrak Tanaman Gonda (Sphenoclea zeylanica Gaertner) dengan Metode Spektrofotometri UV-Vis - Wintariani, Ni Putu; Lionita, Ni Kadek Vinka (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2023)
Free radicals are unstable atoms that can damage cells, causing disease and aging of the skin. Ultraviolet rays cause skin to darken and wrinkle as free radicals produce excess melanin. One of the anti-radical substances is found in the Gonda plant (Sphenoclea zeylanica Gaertner). The plant extract is made into a sunscreen cream dosage form to protect the skin from the dangers of free radicals from sunlight. The aim of this study was to determine the compounds contained in Gonda plant extract and the SPF value of Gonda plant extract sunscreen cream by in vitro method using UV-Vis spectrophotometry. The results showed that Gonda plant extract contains flavonoids, saponins, tannins, steroids, and alkaloids. The SPF value of the cream with 4 concentrations of Gonda plant extract in the formula, namely cream base (0%), F1 (5%), F2 (10%) and F3 (15%) showed the protection category of